495 CONVERSATIONS ON LIVING & DYING: AN INTERVENTION TO INCREASE COGNITIVELY-ABLE, COMMUNITY-BASED FRAIL ELDERS' ENGAGEMENT WITH ACP. (14th June 2021) - Combes, S; Gillett, K; Norton, C; Nicholson, C J
Abstract: Introduction: Advance care planning (ACP) can support person-centred end-of-life care by helping individuals articulate their end-of-life preferences. Frail elders' vulnerability to deterioration makes ACP engagement particularly relevant; however, their engagement with ACP is uncommon. This study aimed to develop an intervention to increase ACP engagement with cognitively-able, community-dwelling frail elders. Methods: Multiple methods were used to establish ACP barriers and facilitators: a systematic integrative review, modified e-Delphi survey (multidisciplinary health and social care professionals (H&SCPs) n = 73), and semi-structured interviews (frail elders n = 10, family members n = 8). A conceptual model, developed from the integrative review, underpinned data collection for the e-Delphi and interviews. Triangulation, including patient and public involvement, was then used to identify H&SCPs behaviours that needed to change and decide intervention content and implementation. The intervention was developed using behavioural change theory. Prototype refinement consisted of pre and post questionnaires, use of the intervention in practice, and focus groups (H&SCPs n = 26). Results: The prototype intervention consists of a 3.5-hour training and education session for H&SCPs, supported by a toolkit. The intervention focuses on the relevance and experience of ACP for frail elders and ACP strategies H&SCP can use to encourage frail elders' ACP engagement. Strategies include recognising the importance of decision-making in relationships and living well now, starting early, using an honest but gentle approach, and helping frail elders prepare for ACP conversations. Participants report that the intervention helps them think differently about ACP and encourages them to engage frail elders with ACP. Conclusions: To our knowledge this is the first intervention underpinned by behaviour theory that focuses on supporting H&SCPs to engage community-dwelling, cognitively-able frail elders with ACP. Refinements, such as additions to the toolkit, have been suggested. However, H&SCPs appear to find the intervention acceptable, feasible, engaging, and useful in their practice.